Medial to posterior release procedure after failure of functional treatment in clubfoot: A prospective study. (April 2016) - Bocahut, Nicolas; Simon, Anne-Laure; Mazda, Keyvan; Ilharreborde, Brice; Souchet, Philippe
Abstract: Purpose: Two conservative techniques for clubfoot treatment are still being debated and depend upon the institution's expertise. For >40 years, the current institution has been a pioneer in the development of the physiotherapy method; however, some severe deformities remain resistant to this method which causes pain, sprains, and difficulties wearing shoes. Therefore, a surgical approach was developed simultaneously for the treatment of these residual or recurring clubfeet. The procedure reproduces the same chronological steps by performing forefoot derotation before correcting hindfoot equinus. The aim of the current study was to assess the results of this surgical technique. Methods: All clubfeet undergoing surgery between October 1995 and February 2009 were prospectively included. Initial severity was based on Dimeglio's classification and final outcomes on the International Clubfoot Study Group (ICFSG) outcome evaluation system. Last follow-up results were assessed by physical examination and radiographs. Results: A total of 137 patients with severe clubfeet (mean Dimeglio score 12.0) underwent surgery. At the mean follow-up of 10.8 years, mean ICFSG score was 4.3 (range 0–23), and 12 % required revision surgery. The rate of undercorrection and overcorrection was low (17 pes-plano-valgus ft and 11 ft with undercorrection). Eight feet had a fixed deformity. Conclusions: Severe deformities are more resistant to conservative techniques even for institutions with large experience. These deformities require further treatment, including surgery if necessary. The medial to posterior soft-tissue release is a valuable technique with stable results. Level of evidence: Level IV.